EFFECTIVENESS OF BELUNTAS EXTRACT GEL (Pluchea indica) ON THE GROWTH OF Porphyromonas gingivalis - Irma Dewi Ratnawati; Budi Suhartono; Lulu Sa’adah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Periodontal disease is common in Indonesia, especially periodontitis, with a prevalence of 74.1%. One of the main etiologies of periodontitis is Porphyromonas gingivalis which colonizes dental plaque in the stages of secondary colonization and maturation. Pluchea indica leaves contain active substances with antibacterial properties, including flavonoids, tannins, alkaloids, saponin, and atsiri oil which can be used as additional pharmacotherapeutic therapy in the treatment of periodontitis. The gel preparation has good dispersion, practical, easy to apply. Aim the study to specify the effectiveness of Pluchea indica extract gel 40%, 60% and 80% against the growth of Porphyromonas gingivalis. Method: This research employed an in vitro experimental post-test control design. Thirty samples were split into five groups: the 40%, 60%, and 80% concentrations of the Pluchea indica leaves gel, positive control using metronidazole gel, and negative control. Samples underwent 48 hours of incubation. After being administered a Pluchea indica leaves gel, the diffusion method is used to determine the sensitivity of the test bacteria to antibacterial. Result: The diameter of the inhibition zone formed by Pluchea indica extract gel group with a concentration of around 80% was in the category very strong. Based on the results of the Tukey post-hoc test p